2021
DOI: 10.3390/catal11111336
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Reduced-Graphene-Oxide-Supported CoPt and Ag Nanoparticles for the Catalytic Reduction of 4-Nitrophenol

Abstract: Composite nanostructure materials are widely used in catalysis. They exhibit several characteristics, such as the unique structural advantage and the synergism among their components, which significantly enhances their catalytic performance. In this work, CoPt nanoparticles and reduced-graphene-oxide-based nanocomposite catalysts (rGO/CoPt, rGO/CoPt/Ag) were prepared by using a facile co-reduction strategy. The crystalline structure, morphology, composition, and optical characteristics of the CoPt nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…CoPt, rGO/CoPt, and rGO/CoPt/Ag catalysts showed a reduction time of 8, 4, and 1 min [15]. A volume of 0.1 mL of 4-NP, 0.005 mol/L and 2 mL of deionized water was added to the quartz cuvette.…”
Section: Reduction Of 4-np To 4-ap Using Synthesized Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…CoPt, rGO/CoPt, and rGO/CoPt/Ag catalysts showed a reduction time of 8, 4, and 1 min [15]. A volume of 0.1 mL of 4-NP, 0.005 mol/L and 2 mL of deionized water was added to the quartz cuvette.…”
Section: Reduction Of 4-np To 4-ap Using Synthesized Materialsmentioning
confidence: 99%
“…The CoPt alloys are one of the most studied materials due to their possible applications in BPM (Bit Patterned Media) for high-density magnetic recording [9,10], microelectromechanical systems (MEMS) for sensing and actuating devices [9,11], Magnetic Resonance Imaging (MRI) contrast agents [1,12], or as catalysts [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high specific surface area of rGO is beneficial for the loading of nanoparticles, thus improving the dispersion of particles on rGO nanosheets [34]. Moreover, many studies have demonstrated the presence of a synergistic effect between rGO and the anchoring particles, which can significantly enhance the catalytic performance [35,36]. For example, Co 3 O 4 nanocrystals grown on rGO showed surprisingly high catalytic activity for oxygen reduction reaction and oxygen evolution reaction because of the synergetic chemical coupling effects between Co 3 O 4 nanocrystals and graphene [37].…”
Section: Of 18mentioning
confidence: 99%
“…The CoOOH/rGO nanocomposite served as the catalyst to relay active hydrogen species and electrons from the adsorbed donor (BH 4 − ) to the adsorbed acceptor (p-NP) nearby, thereby triggering the reduction reaction. Therefore, the efficient adsorption performance for p-NP and BH 4 − as well as its excellent electron transport ability, are the key factors for a catalyst to have superior activity [36]. In addition, Qu et al have demonstrated that, for the catalytic hydrogenation of p-NP, increasing the amount of reactants adsorbed on the catalyst surface is beneficial in improving the catalytic performance [47].…”
Section: Catalytic Reduction Of P-nitrophenolmentioning
confidence: 99%